Optimizing the Potential of Dayah Putri Muslimat Samalanga as the Basis for Economic Empowerment of the Ummah - Muhammad Kharazi (Wasatha: Jurnal Studi Islam dan Humaniora, 2023)
Dayah Putri Muslimat Samalanga is a dayah who has an interesting phenomenon from dayah activities in general, usually what is more prominent than dayah activities are educational and da'wah activities. However, Dayah Putri Muslimat Samalanga actually combines economic or business activities that are pretty advanced and even becomes a model of an independent Islamic boarding school and can foster a spirit of independence for students in the economic field. This study aims to find out how to optimize the potential of the dayah as a basis for empowering the people's economy. The type of research used is case study research with a qualitative approach. The data collection methods used in this study were observation, interviews, and document studies where the author saw directly the situation in the field. The analysis technique used in this study uses the interactive model of Miles and Huberman in the form of collecting data first, then processing the data, simplifying and focusing the data. The research results obtained by Samalanga Muslimat Dayah are rich in potential and resources considering the number of students in Samalanga Muslimat Dayah has reached thousands. The business units formed by female dayah Putri Muslimat Samalanga include travers, canteens, coffee shops, cooperatives, telecom stalls, agriculture, animal husbandry, and plantations. However, the management is still not optimal, because it is not well organized (unorganized business). The efforts to optimize the potential of existing resources are through education, training, and resource assistance related to business management.